Global surgery is stronger when infection prevention and control is incorporated: a commentary and review of the surgical infection landscape - Chandler Hinson; Claire Kilpatrick; Kemal Rasa; Jianan Ren; Peter Nthumba; Robert Sawyer; Emmanuel Ameh (BMC Surgery)
Abstract Incorporating infection prevention and control (IPC) is crucial for strengthening global surgery, particularly in low- and middle-income countries (LMICs). This review article highlights the critical role IPC plays in ensuring equitable and sustainable surgical care, aligning with the Sustainable Development Goals (SDG) 3 and 10, which aim to promote health and reduce inequalities. Surgical site infections (SSIs) and other healthcare-associated infections (HAIs) disproportionately affect LMICs, where IPC infrastructure is often underdeveloped. Without robust IPC measures, surgeries in these regions can result in higher morbidity, mortality, and healthcare costs, exacerbating disparities in healthcare access and outcomes. Despite global efforts, such as the World Health Organization (WHO) Guidelines on the Prevention of Surgical Site Infections, IPC integration in surgical practices remains inconsistent, particularly in resource-constrained settings. More widespread adoption and implementation are necessary. By embedding IPC within global surgery frameworks, health systems can improve surgical outcomes, reduce costs, and enhance the resilience of healthcare systems. Effective IPC reduces extended hospital stays, limits the spread of antimicrobial resistance, and increases trust in surgical services. Moreover, the cost savings from preventing SSIs are substantial, benefiting both healthcare systems and patients by reducing the need for prolonged care and antibiotic treatments. This review article calls for greater integration of IPC measures in global surgery initiatives to ensure that surgical interventions are both life-saving and equitable. Strengthening IPC is not optional but essential for achieving the broader goals of universal health coverage and improving public health outcomes globally.